Development of an XML-based structural product retrieval system for virtual enterprises - Tsai, Chieh-Yuan; Tien, Fang-Chih; Pan, Tsung-Yu (International journal of production research, 2004)
A single company cannot survive in today's global business environment without collaborating with others. A virtual enterprise is good practice for sharing core resources, experiences and information between companies with the same business goal. Through sharing product information, a company can prevent unnecessary spending in developing similar products that already exist. Although some attempts have been made to facilitate product searches, these methods are typically not suitable for structural product searches under virtual enterprise environments. In this work, an XML (eXtensible Markup Language) based structural product retrieval system for virtual enterprises is proposed to conquer this deficiency. A structural product is first transformed into component strings using a structure parsing algorithm. The structural similarity measurement between a product query and target product is designated and evaluated using a component matching algorithm and fuzzy mode composition. XML technology is used as the data exchange standard so that variant product information can be exchanged smoothly among heterogeneous database platforms. A comparison with a general Boolean search approach shows that the proposed structural search method can help users find desired product information more quickly and correctly. It is believed that virtual enterprise partners can benefit from using this system to increase their competitive advantage.